Pengaruh tumpatan Atraumatic Restorative Treatment (ART) menggunakan bahan Glass Ionomer Cement terhadap pH saliva pada Anak Sekolah Dasar - Yuniarly, Etty; Rochmawati, Desi (Poltekkes Kemenkes Yogyakarta, 2020)
On school children, dental caries is an important problem because it is not only causeing pain complaints, but also spreads infection to other parts of the body with the result in decreased productivity. This condition will certainly reduce the frequency of children's attendance to school, disrupt the concentration of learning, affect appetite and food intake so that it can affect nutritional status and ultimately can lead to impaired physical growth. This study used Quasi Experimental, with One Group Pre and Post Test design method. This research was conducted at Balangan I Elementary School and Nglengking Public Elementary School, Minggir, Sleman, Yogyakarta. The sampling technique used purposive sampling method. The Data collection used the restriction of Atraumatic Restorative Treatment by using Glass Ionomer Cement material and salivary pH measurement. The data analysis technique used Paired Test and Anova test analysis. Prior to the filling of Atraumatic Restorative Treatment (ART) by using Glass Ionomer Cement salivary pH criteria acid as much as 53.3%, after clogging by measuring salivary pH for 1 minute to 5 minutes, there was a decrease in salivary pH criteria acid from 45% to 25% and an increase in salivary pH of the criteria alkali from 25% to 38.3%. The result of Paired Test was ?-value = 0,000, meaning that there were differences in salivary pH before and after the filling of Atraumatic Restorative Treatment (ART) for 1 minute to 5 minutes by using Glass Ionomer Cement material, whereas the result of Anova test was ?-value = 0.581> 0.05 then Ho was accepted, which meant that there were no significant differences in average Salivary pH score within 1 minute to 5 minutes after the filling of Atraumatic Restorative Treatment with Glass Ionomer Cement material. The filling of Atraumatic Restorative Treatment (ART) by using Glass Ionomer Cement material affect the salivary pH.